Ambiguitas tafsir feminis di Indonesia - Mahbub Ghozali (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2020)
Interpretation is a major component in providing arguments about gender equality in Islam. Interpretation as an explanation of the Qur'an provides for everyone to form their religious behavior. For example the biased interpretation of surah al-Nisâ (4): 1 which explain about relationship between women and men. Some feminist reviewers in Indonesia respond to these interpretations which resulting in several trends. On the basis of this, this study aims to identify some of the trends generated by feminist reviewers in Indonesia by limiting a number of figures, namely M. Qurasih Shihab, Nasaruddin Umar, Husein Muhammad, Faqihuddin Abdul Kodir, Musdah Mulia, and Zaitunah Subhan by using Gadamer's hermeneutic method. This study found that there were two trends by the feminist reviewers. First, the tendency of interpretation which involves the discourse of the text to find the main idea (world view) of the text, so that the resulting interpretation has a moderate tendency. Second, the tendency of interpretation by involving the discourse of feminism to approach the text (verse), thus producing a new paradigm in the interpretation of misogynistic verses. This tendency is caused by the different set of knowledge used in interpreting the verse. projections of knowledge possessed produce tendencies in interpretation.